Spreading of fibroblasts in medium containing cytochalasin B: formation of lamellar cytoplasm as a combination of several functional different processes. - Bliokh, Z L (1980)
Normal cultured mouse fibroblasts spreading on solid substrate extend and attach numerous pseudopods; lamellar cytoplasm is eventually formed from the attached pseudopods. Fibroblasts spreading in the presence of cytochasin B (CB) from de novo a system of arbor-like branched processes rather than lamellar cytoplasm. The growing and fully formed arbor-like processes, in contrast to normal lamellar cytoplasm, have low contractility and are unable to clear patched concanavalin A receptors from their surfaces; their attachement sites are not associated with microfilament bundles. The cells spreading in medium containing CB and Colcemid do not form well-organized branched structures but extend and attach numerous unstable pseudopods. It is suggested that normal formation of lamellar cytoplasm can be regarded as a combination of several functionally different processes: (a) of rudimentary pseudopodial reactions resistant to CB and Colcemid; (b) of CB-sensitive lamellization; and (c) of Colcemid-sensitive stabilization.